1994
DOI: 10.1164/ajrccm.149.6.8004296
|View full text |Cite
|
Sign up to set email alerts
|

Effective allergen avoidance at high altitude reduces allergen-induced bronchial hyperresponsiveness.

Abstract: We studied the effects of reduced allergen exposure on bronchial hypereactivity (BHR) in two groups of asthmatic children allergic to house dust mites (HDM) living at high altitude for 9 continuous mo. In the first group the serum levels of total and HDM-specific IgE showed significant decreases after 3 mo (p < 0.001 and p < 0.02, respectively) and after 9 mo (p < 0.001). Three months after returning home the total IgE levels had increased significantly (p < 0.001). The mean percentage fall in peak expiratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
106
0
6

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(113 citation statements)
references
References 24 publications
1
106
0
6
Order By: Relevance
“…High-altitude treatment has been applied for decades in patients with asthma, especially in children and adolescents with moderate-tosevere atopic disease [6][7][8][9]. The success of this treatment has long been attributed to the absence of house dust mite allergens at altitudes .1,600 m [10].…”
mentioning
confidence: 99%
“…High-altitude treatment has been applied for decades in patients with asthma, especially in children and adolescents with moderate-tosevere atopic disease [6][7][8][9]. The success of this treatment has long been attributed to the absence of house dust mite allergens at altitudes .1,600 m [10].…”
mentioning
confidence: 99%
“…Hospitalizing patients in a house-dustmite-free environment resulted in an improvement in airway responsiveness and a reduction in the medication requirement of a few adults (24). Moreover, removal of house-dust-mite-sensitized children to a low-allergen environment decreased airway hyperresponsiveness and abated asthma (25,26). However, the low-allergen environment must be maintained because these children did not maintain their improvement on returning home.…”
mentioning
confidence: 99%
“…25 Other similar studies assessed changes of environment in which patients were moved to high altitude places where mite levels were low; in these cases, sensitized patients also improved. [26][27][28] A recent prospective study analyzed environment care measures for children at risk since birth, and demonstrated that there was no difference in sensitization to air allergens between the cared group and controls (in which no environmental measures were undertaken); there was, however, a difference in lung function between groups at age 3 years. 38 Studies that aimed to decrease allergen exposure in households reached conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme-linked immunosorbent assay (ELISA) was used for detecting the Der p 1, Der f 1, Can f 1 and Fel d 1 allergens as described by Luczynska et al 37 modified by Sopelete et al 28 The following monoclonal antibodies (mAb) for capture were used: anti-Der p 1 (clone 5H8), anti-Der f 1 (clone 6A8), anti-Fel d 1 (clone 6F9), and anti-Can f 1 (clone 6E9); the concentration was 10 mg/ml in a carbonate-bicarbonate buffer at 0.06M and pH 9.6. Detection was done using biotinilated mAb, as follows: anti-Der p 1 and anti-Der f 1 (4C1), anti-Fel d 1 (3F4C4) and polyclonal rabbit serum anti-Can f 1 at 1:500.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation